Micro-founded measurement of regional competitiveness in Europe - Gábor Békés; Gianmarco I. P. Ottaviano (Hungarian Academy of Sciences, Institute of Economics, 2015)
Enhancing competitiveness is a popular target in economic policy making - not only at the national, but at the regional level as well despite neither generally accepted definition nor any strong agreement on how to measure it. In this chapter we discuss the conceptual underpinnings of why it is interesting to unpack the economic performance of a country into the economic performance of its regions. We argue that as firms compete; measuring regional competitiveness should be also based on comparing firm performance across EU regions. Given available data, we propose a new way to gauge how firms fare is to look at their ability to access and penetrate world markets. The key index is export per worker from a region to non-EU destinations relative to the EU average - a 'regional competitiveness' index that captures the capacity of a region's firms to outperform the firms of the average EU region in terms of exports.
Keywords: R11; F14; R58; 330; export; regional competitiveness; measurement; granularity